Study of risk factors associated with breast cancer: a case control study - Jadhao, Ashok R.; Sharma, B. K.; Jadhao, Sanjivani A.; Tayade, Hitesh C. (International Journal Of Community Medicine And Public Health, 2021)
Background: Developing countries are facing double burden of infectious and non-communicable diseases. Omran gave epidemiological transition theory, which can be seen in India also. Lifestyle changes made Indian prone to non-communicable diseases. Cancer is among the most common non communicable diseases in India. Breast cancer contributes one fourth of all cancer burden in India. It is noted that more number of cases are being seen in 25 to 40 years age group. Objective of the study was to study risk factor associated with breast cancer. Methods: Hospital based case control study was conducted in tertiary cancer centre from July 2017 to December 2019. Sample size of 96 cases was calculated, though 100 cases was interviewed and similar number of age group matched controls was selected. Sociodemographic, past history of benign breast lesion, family history of breast cancer, body mass index, waist to hip ratio and reproductive risk factors was assessed. Results: The significant risk factors on multiple logistic regression were (adjusted odds ratios with 95% CI) age at menarche ≤11 years (1.16, 1.025–1.451), waist to hip ratio more than 0.85 (1.61, 1.473–1.963) and history of abortion (1.14, 1.006–1.366). Conclusions: Women with early age of menarche, higher waist to hip ratio and history of abortion were found to be at higher risk of developing breast cancer. Annual screening of high risk women, teaching self-breast examination to all women and promoting physical activity to maintain waist to hip ratio less than 0.85 should be done.